The Competence of Preachers in Preaching (A Study of the Local Leadership Council) of Wahdah Islamiyah Makassar - Hastuti; Jamaluddin (Jurnal Mercusuar, 2022)
The main problem of this research is how is the competence of preachers (mubalig) in preaching at the Regional Leadership Council (Dewan Pimpinan Daerah/DPD) of Wahdah Islamiyah Makassar? This main problem is then broken down into several sub-problems or research questions, namely: how is the substantive competence of preachers in preaching at the DPD of Wahdah Islamiyah Makassar? This is a qualitative research with a communication approach. The data sources of this research are the Chairman of DPD Wahdah Islamiyah Makassar, the Secretary of DPD Wahdah Islamiyah Makassar, the Head of the Preaching Department, preachers (mubalig), and the audience (mad'u). The data collection methods used are observation, interviews, documentation, and reference tracing. The data processing and analysis techniques are conducted through three stages: data reduction, data presentation, and conclusion drawing. The results of this research show that the substantive competence of preachers in DPD Wahdah Islamiyah Makassar can be seen from their educational level, which ranges from level 3, level 2, level 1, and the lowest being high school, even some of them hold the title of professor. In addition, some preachers are alumni of universities in the Middle East.